2020
DOI: 10.1002/adem.202000825
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Tuning of Near‐Field Radiative Thermal Rectification

Abstract: Taking advantage of phase‐transition and reconfigurable metamaterials, dynamic control of nanoscale thermal modulation can be achieved through the near‐field radiative thermal rectification devices. Herein, an active‐tuning near‐field thermal rectifier using reconfigurable phase‐transition metamaterials is explored. The rectifier has two terminals separated by vacuum, working under a controllable operational temperature around the critical temperature of the phase‐transition material VO2. One of the terminals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…These materials undergo a sudden and drastic change in their optical properties around their critical temperature. Among these materials, metal-insulator transition (MIT) materials have attracted significant attention to design radiative heat rectifiers [27][28][29][30][31][32][33][34]. A widely MIT material is vanadium dioxide (VO 2 ) which undergoes its phase transition at T c ≈ 340 K [35,36].…”
Section: Rectificationmentioning
confidence: 99%
“…These materials undergo a sudden and drastic change in their optical properties around their critical temperature. Among these materials, metal-insulator transition (MIT) materials have attracted significant attention to design radiative heat rectifiers [27][28][29][30][31][32][33][34]. A widely MIT material is vanadium dioxide (VO 2 ) which undergoes its phase transition at T c ≈ 340 K [35,36].…”
Section: Rectificationmentioning
confidence: 99%
“…When the distance between two objects is comparable to or less than the thermal wavelength, the photon tunneling effect plays an essential role in the thermal radiative transfer, greatly enhancing the near-field radiative heat transfer (NFRHT) past the Planckian blackbody limit by several orders of magnitude [1][2][3][4][5][6]. Numerous theoretical studies on the NFRHT between various materials and nanostructures have been performed, such as transfer between two planar surfaces [1,7,8], two nanoparticles [8,9], two gratings [10][11][12][13][14], one sphere and plane [15], three bodies [16], and so on [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Recently, many experimental reports have indicated that the NFRHT can exceed the blackbody limit for a plane-plane configuration [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many experimental reports have indicated that the NFRHT can exceed the blackbody limit for a plane-plane configuration [33][34][35][36][37][38]. Therefore, NFRHT is of great significance in a variety of engineering applications, such as energy management [17,[39][40][41][42], sensing, and micro/nano-electromechanical systems (M/NEMS) [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…This thermal rectification exploits the thermal dependence of optical properties of the materials in interaction [79][80][81][82], which naturally breaks the symmetry in the heat transport when the sign of the temperature gradient between the two solids is changed. In addition, a large asymmetry in the heat transport was reported in systems made with materials undergoing a phase change, such as metal-insulator transition materials [83][84][85][86][87][88][89][90][91][92][93][94][95][96] and normal metal-superconductor transition materials [97][98][99]. However, this strong rectification occurs only close to the critical temperature of these materials.…”
Section: Introductionmentioning
confidence: 99%